HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN PERTUMBUHAN ANAK USIA 3-5 TAHUN DI POSYANDU KASIH IBU WILAYAH KERJA PUSKESMAS BALOI KOTA BATAM - Purwati, Kasih; Yulia, Luis; Rachmah, Aulia Premita (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background: Growth is an increase in the size and number of cells and intercellular tissues, which includes an increase in physical size and body structure both partially and completely. Children who face obstacles in their growth can affect their future growth. The success of preventing late growth of children is influenced by basic knowledge that is good for mothers. To achieve effective communication between mother and child, it is necessary to pay attention to maternal attitudes that reflect positive interactions and are responsive to monitoring toddler growth. The purpose of this study is to determine the relationship between mothers' attitudes and knowledge with the growth of children aged 3-5 years at the Posyandu Kasih Ibu working area of the Baloi Health Center in Batam city in 2023. Methods: This type of research is quantitative using an analytical observational research design, with a cross sectional approach. The population in this study is mothers who have children aged 3-5 years at the Posyandu Kasih Ibu Working Area of the Baloi Health Center in Batam City. Results: The results of the Chi-Square analysis of the relationship between maternal attitudes and the growth of children aged 3-5 years were obtained p = 0.001 and the relationship of maternal knowledge with the growth of children aged 3-5 years was obtained p = 0.001 where Ho was rejected and H1 was accepted. Conclusion: Based on the results of the study, it was found that there is a relationship between the knowledge and attitudes of mothers with the growth of children aged 3-5 years at the Posyandu Kasih Ibu in the Baloi Health Center Work area in Batam city in 2023.